Electricity Distribution Tenders and Media - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2018)
The purpose of this study which considers media corporations as commercial and industrial organizations is to specify how media ownership structure and their relations to the government influence news content. Throughout the 2000s, energy sector has become one of the areas of interest of the large capital - which also consists of media owners-as a result of the restructuring and fulfillment of the legal infrastructure for privatization of the Public Economic Enterprises (PEEd) which had been in natural monopoly position until then. Nowadays, almost all prominent media organizations have investments on energy sector. Some of these organizations have applied to electricity distribution tenders. In this direction, the news report, opinion columns and interviews about BEDAS, Gediz EDAS, Dicle EDAS and Trakya EDAS tenders which occurred on 9th August 2010 are analyzed based on quantitative and qualitative content analysis. It is observed that media organizations investing in the energy sector treat these tenders - which have many dimensions relevant and influential to all segments of society independently from political and economical processes by disregarding the relations of social distribution.
Keywords: Media; Political Economy; Privatization; Energy; Quantitative and Qualitative Content Analysis